ШИМОЛИ – ҒАРБИЙ ЎЗБЕКИСТОН ЧЎЛ ҲУДУДЛАРИ ВИЗИЛДОҚ ҚЎНҒИЗЛАРИ (COLOEPTERA: CARABIDAE) ФАУНАСИ - Ешмуратов, А.Я.; Холматов, Б.Р.; Гулимбетов, Б.Д. (SCIENCE and SOCIETY, 2020)
In the studied sandy deserts of nortthern -western Uzbekistan, there are found 50 species of beetles belonging to 26 genera, including 22 species from the Aral sea and 43 species from the Kyzylkum. The bio topic distribution of desert areas of identified beetles has been shown to be more sensitive to changes in landscapes, primarily due to abiotic, hydro-edaphic and biotic factors of the environment and as an indicator under these conditions. The study of the ecology of beetles by regions allows them to be used in the practice of biological control of harmful species.